Falling from grace downward mobility in the age of affluence - Newman, Katherine S., 1953- (University of California Press, 1999)
Over the last three decades, millions of people have slipped through a loophole in the American dream and become downwardly mobile as a result of downsizing, plant closings, mergers, and divorce: the middle-aged computer executive laid off during an industry crisis, blue-collar workers phased out of the post-industrial economy, middle managers whose positions have been phased out, and once-affluent housewives stranded with children and a huge mortgage as the r.